2020
DOI: 10.21203/rs.3.rs-88256/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Purslane (Portulaca Oleracea L.) Promotes the Growth Performance of Broilers by Modulation of Gut Microbiota

Abstract: Purslane is a widespread wild vegetable with both medicinal and edible properties. It is highly appreciated for its high nutritional value and is also considered as a high-quality feed resource for livestock and poultry. In this study, Sanhuang broilers were used to investigate the effect of feeding purslane diets on the growth performance in broilers and their gut microbiota. A total of 48 birds with good growth and uniform weight were selected and randomly allocated to four treatment groups A (control), B, C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This reason results in an improvement in intestinal microecology. Also, Wang et al, (2021) found that the gut microbiota of Sanhuang broilers was largely consisted of Gallibacterium, Bacteroides, and Escherichia-Shigella , among other bacteria, according to microbial diversity study. Lactobacillus counts increased considerably as purslane concentration increased, whereas Escherichia-Shigella counts decreased.…”
Section: Discussionmentioning
confidence: 96%
“…This reason results in an improvement in intestinal microecology. Also, Wang et al, (2021) found that the gut microbiota of Sanhuang broilers was largely consisted of Gallibacterium, Bacteroides, and Escherichia-Shigella , among other bacteria, according to microbial diversity study. Lactobacillus counts increased considerably as purslane concentration increased, whereas Escherichia-Shigella counts decreased.…”
Section: Discussionmentioning
confidence: 96%
“…A total of two articles were conceptual papers Guenther et al, 2014), and 24 articles did not discuss the determinants of cost stickiness but instead used them as independent variables. These articles have not been used because they discuss the effects of cost stickiness on, for example, the forecasting of earnings (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). Be cause our focus is the managers' behaviour, we have dropped 15 articles that discuss, for example, the effect of an auditor's choice, ac counting policies, changes in office address, CEO structure, and changes in the research sample on cost stickiness (Chae & Chung, 2015;Chae & Ryu, 2016;Chung et al, 2019;Ibrahim, 2018;Lee et al, 2019;Loy & Hartli eb, 2018;Shust & Weiss, 2014;Xue & Hong, 2016;Yang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As users of cost account ing information, we need to understand the causes of the asymmetry of cost behaviour, especially cost stickiness. Studies have even shown that cost stickiness (CS) affects the company's stock performance (Ciftci et al, 2016;Ciftci & Salama, 2018;Kaspereit & Lopatta, 2019;Lopatta et al, 2020;Lu et al, 2020;Tang et al, 2020;Weiss, 2010). The asymmetry of cost behaviour is due to individual management considerations in ma king decisions.…”
mentioning
confidence: 99%